Editorial - Rua Castañeda, Sohely (Cooperativismo & Desarrollo, 2023)
From their role of management and dissemination of knowledge, space for dialogue and production framework, academic journals have fulfilled a mission alongside social movements, a mission that goes beyond making a set of knowledge accessible. Today, we are going through a particular moment for solidarity economy and cooperativism, which brings various challenges for the sector and the social movement, from the search for a solution to different long-term problems in society to the deepening of poverty and inequality that the covid-19 pandemic has caused around the world.